Operative vs Nonoperative Treatment of Achilles Tendon Ruptures Using Early Functional Rehabilitation: Critical Analysis of Evidence. (July 2022) - Reito, Aleksi; Mattila, Ville; Karjalainen, Teemu
Background: Nonoperative treatment with functional rehabilitation of Achilles tendon ruptures (ATRs) has become more common because of claim of "equivalent" risk of rerupture compared to operative treatment. We investigated how current evidence corroborates the often-claimed "equal" or "nondifferent" complication rates. Methods: A search of meta-analyses in PubMed, CENTRAL, and Scopus was performed. Meta-analyses including randomized controlled trials (RCTs) comparing open operative repair of ATR and nonoperative treatment with functional rehabilitation regarding reruptures and other complications were identified. Results: Four separate meta-analyses with 6 pooled treatment comparisons were identified. One of the 6 treatment effects (for risk ratio [RR]) showed a reduced risk of rerupture favoring operative treatment, whereas in the remaining analyses the null hypothesis assuming equal risk or an RR of 1 could not be rejected. The smallest RR (benefit in favor of surgery) that could be rejected based on the 95% CI was 0.28. The smallest risk difference that could be rejected in favor of surgery was 6.4%, indicating that nonoperative may have up to 6.4% higher rerupture rate. Treatment effects for complications other than rerupture had very large variability and imprecision. Conclusion: The literature comparing surgery with nonoperative treatment using functional rehabilitation in ATR have been interpreted in favor of nonoperative treatment as the rerupture rates were falsely considered "equivalent." None of the published meta-analyses excluded a relative risk that is likely to affect the course of treatment in many cases. Increasing incidence of nonoperative treatment in ATRs is not clearly supported by current evidence.